Uncovering the Pharmacology of Xiaochaihu Decoction in the Treatment of Acute Pancreatitis Based on the Network Pharmacology - Zhan, Lianghui (Biomed Res Int, 2021)
BACKGROUND: Xiaochaihu decoction (XD) has demonstrated the pharmacodynamics on acute pancreatitis. This study was aimed at investigating the material and molecular basis of Xiaochaihu decoction. METHODS: Firstly, compounds of seven herbs containing XD were collected from the TCMSP, ETCM, and BATMAN-TCM databases, and the putative targets of pancreatitis were obtained from the OMIM, TTD, and GeneCards databases. Then, the PPI network was constructed according to the matching results between XD potential targets and pancreatic neoplasm targets. Furthermore, enrichment analysis on GO and KEGG by DAVID utilized bioinformatics resources. Finally, molecular docking was performed to simulate the interaction between the active compound of XD and putative targets. In an in vitro experiment, AR42J cells were induced by LPS and then treated with Quercetin (25, 50, and 100 μM) or XCHD. The IL-6, TNF-α, and IL-1β levels were detected by ELISA kit, MAPK3 and TP53 mRNA expressions were measured by qRT-PCR, and the proteins of MAPK3 and TP53 expressions were measured by WB. RESULTS: A total of 196 active ingredients and 91 putative targets were selected. The PPI network analysis demonstrated that Quercetin was the candidate agent and MAPK3, IL-6, and TP53 were the potential targets for the XD treatment of acute pancreatitis. The KEGG analysis revealed that pathways in cancers, TNF signaling way, and MAPK signaling way might play an important role in pancreatitis therapy. And molecular docking results showed that Quercetin combined well with MAPK3, IL-6, and TP53. An in vitro experiment indicated that XCHD and Quercetin inhibited the IL-6, TNF-α, and IL-1β levels and MAPK3 and TP53. CONCLUSION: This study illustrated that XCHD and Quercetin contained in XD played an important role in the treatment of acute pancreatitis by acting on the key genes of MPAK3, IL-6, and TP53 which were associated with inflammation and apoptosis.